Comparative adsorption mechanism of rice straw activated carbon activated with NaOH and KOH - Mohamad Jani Saad,; Mohd Shaiful Sajab,; Wan Nazri Wan Busu,; Sufian Misran,; Sarani Zakaria,; Siew, Xian Chin; Chin, Hua Chia (Penerbit Universiti Kebangsaan Malaysia, 2020)
Activated carbon (AC) was produced from rice straw via a two-step method. Potassium hydroxide (KOH) and sodium hydroxide (NaOH) were used as activating agent. The activated carbon (AC) samples were used as adsorbent to remove methylene blue (MB) from aqueous solution. Characterizations using a scanning electron microscope (SEM), BrunauerEmmett-Teller surface area (BET), and Fourier transform infrared (FTIR) spectroscopy were performed on the samples before the MB adsorption experiments. The adsorption isotherms and kinetics analyses were carried out under different conditions of pH, temperature, and MB concentration to study the adsorption efficiency of the samples against the MB solution. The adsorption kinetics of both activated carbon samples followed the pseudo-second-order model. The adsorption capacity of the KOH rice straw activated carbon towards MB achieved a maximum adsorption 588 mg/g as compared to 232 mg/g of the NaOH rice straw activated carbon. The intraparticle diffusion model indicated that the adsorption process of the activated carbon samples toward MB included the external mass transfer and diffusion of MB molecules into the adsorbents. Adsorption isotherm results for MB on the activated carbon samples fit the Langmuir isotherm, suggesting monolayer adsorption during the adsorption process.